Implementation of an Accelerated Genomic Selection Scheme as the Key Strategy to Enhance Genetic Gain In the ICARDA Durum Wheat Breeding Program - Kabbaj, Hafssa; Kehel, Zakaria; Al-Shamaa, Khaled; Zaim, Meryem; Sall, Amadou T.; Ortiz, Rodomiro; Bassi, Filippo (2024)
This is an oral presentation that was given by Dr. Hafssa Kabbaj during the African plant breeding conference held at the University Mohamed 6 Polytechnics- Bengurir – Morocco from the 23rd to the 26th of October 2023. The title of the presentation is: ‘’Implementation of an Accelerated Genomic Selection Scheme As The Key Strategy To Enhance Genetic Gain In The ICARDA Durum Wheat Breeding Program’’.